Where the wild things are - Sendak, Maurice (New York : Scholastic Inc., 1963)
A naughty little boy, sent to bed without his supper, sails to the land of the wild things where he becomes their king.
"1964 Caldecott award winner" -- p. 4 of cover.
Published by arrangement with Harper & Row.
Keywords: Fantasy -- Juvenile fiction; Monsters -- Juvenile fiction; Caldecott Medal